Electrolytic capacitor
Patent Information
- Application Number
- CN202580023452.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-27
- Filing Date
- 2025-03-19
- Publication Date
- 2026-10-27
AI Technical Summary
[0022]根据本公开,能够得到特性高的电解电容器。
Smart Images

Figure CN122996494A_ABST
Abstract
Description
[0001] Cross-reference of related applications
[0002] This disclosure claims the benefit of priority to Japanese Patent Application No. 2024-051299, filed with the Japan Patent Office on March 27, 2024, the contents of which are incorporated herein by reference in their entirety. Technical Field
[0003] This disclosure relates to an electrolytic capacitor. Background Technology
[0004] As a method for forming the solid electrolyte layer of an electrolytic capacitor, a method of polymerizing monomers on the surface of the dielectric layer has been proposed in the past.
[0005] Patent Document 1 discloses "a solid electrolytic capacitor, characterized in that, in a capacitor element having an anode composed of a porous body of a valve metal selected from tantalum, niobium, and aluminum and a dielectric layer composed of an oxide film of these valve metals, a monomer mixture of 2,3-dihydro-thieno[3,4-b][1,4]dioxane and 2-alkyl-2,3-dihydro-thieno[3,4-b][1,4]dioxane in a molar ratio of 0.05:1 to 1:0.1 is polymerized in the presence of an organic sulfonic acid to form a layer of conductive polymer containing the above-mentioned organic sulfonic acid as a dopant, and the above-mentioned conductive polymer is used as a solid electrolyte."
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent No. 5093915 Summary of the Invention
[0009] The problem the invention aims to solve
[0010] Currently, there is a demand for improved reliability of electrolytic capacitors, including characteristics such as reduced leakage current and improved voltage withstand capability. In this context, one of the objectives of this disclosure is to provide electrolytic capacitors with superior performance.
[0011] Solution for solving the problem
[0012] One aspect of this disclosure relates to an electrolytic capacitor having:
[0013] Anode body with porous sections;
[0014] A dielectric layer formed on at least a portion of the surface of the porous portion; and
[0015] A solid electrolyte layer covering at least a portion of the dielectric layer.
[0016] The solid electrolyte layer comprises a first conductive polymer containing units of a first monomer.
[0017] The first monomer is selected from the following formula (I):
[0018]
[0019] At least one of the compounds shown in the group.
[0020] In the above formula (I), m is an integer from 0 to 10, X is O or S, and R1 is a straight-chain or branched alkyl group.
[0021] The effects of the invention
[0022] According to this disclosure, it is possible to obtain electrolytic capacitors with high performance characteristics. Attached Figure Description
[0023] Figure 1 This is a schematic cross-sectional view of the electrolytic capacitor of Embodiment 1.
[0024] Figure 2 It is a schematic representation Figure 1 A cross-sectional view of a portion of the electrolytic capacitor shown. Detailed Implementation
[0025] The novel features of the invention are set forth in the appended claims, but the invention relates to both its structure and content, and together with other objects and features of the invention, can be better understood by the following detailed description taken in conjunction with the accompanying drawings.
[0026] The following examples illustrate embodiments of this disclosure, but this disclosure is not limited to the examples described below. In the following description, specific numerical values and materials are sometimes illustrated, but other numerical values and materials can be applied as long as the invention of this disclosure can be implemented. In this specification, the description of "numerical value A to numerical value B" includes both numerical value A and numerical value B, and can be replaced with "numerical value A or higher and numerical value B or lower." In the following description, when lower and upper limits of numerical values related to specific physical properties, conditions, etc., are illustrated, any of the illustrated lower limits can be arbitrarily combined with any of the illustrated upper limits, as long as the lower limit does not exceed the upper limit.
[0027] An electrolytic capacitor (hereinafter also referred to as "capacitor (C)") according to one embodiment of this disclosure comprises: an anode body having a porous portion; a dielectric layer formed on at least a portion of the surface of the porous portion; and a solid electrolyte layer covering at least a portion of the dielectric layer. An electrolytic capacitor having a solid electrolyte layer may also be referred to as a "solid electrolytic capacitor". It should be noted that "capacitor" can also be replaced with "capacitor".
[0028] A porous portion is provided at least in the surface layer of the anode body. The entire anode body may also be porous. The capacitor (C) may have an anode wire having an embedded portion embedded in the anode body and a protrusion extending outward from the anode body.
[0029] Hereinafter, the smallest unit of an electrolytic capacitor, which includes an anode, a dielectric layer, and a solid electrolyte layer, is sometimes referred to as a "capacitor element." The concept of a capacitor (C) encompasses both electrolytic capacitors and capacitor elements.
[0030] An electrolytic capacitor (or capacitor element) is divided into an anode section and a cathode section. The anode body constitutes the anode section. The solid electrolyte layer constitutes the cathode section. The anode section and the cathode section are insulated by a dielectric layer. The cathode section contains at least the solid electrolyte layer and may also contain a cathode lead-out layer.
[0031] The anode section may also include an anode body and an anode wire. The anode body may be a porous sintered body or a metal foil with a porous surface.
[0032] A dielectric layer is formed on at least a portion of the surface of the anode body. The dielectric layer is formed, for example, by chemically converting the anode body, causing an oxide coating to grow on the surface of the anode body. In the chemical conversion process, the anode body can also be anodized by immersing it in a chemical conversion solution. The oxide coating can also be formed using a vapor-phase method such as atomic layer deposition (ALD). Alternatively, the anode body can be oxidized by heating it in an oxygen-containing atmosphere.
[0033] A solid electrolyte layer is disposed between a dielectric layer formed on the surface of the anode and a cathode lead-out layer. Here, the solid electrolyte layer comprises a first conductive polymer containing units of a first monomer. It should be noted that the term "unit" in "unit of the first monomer" refers to the smallest unit of the structural portion of the polymer derived from the first monomer. Hereafter, regardless of the type of polymer or monomer, the term "unit" of the monomer in the polymer will be defined with the same meaning.
[0034] The first monomer is selected from the following formula (I):
[0035]
[0036] At least one of the compounds shown in the group.
[0037] In formula (I), m is an integer from 0 to 10, X is O (oxygen atom) or S (sulfur atom), and R1 is a straight-chain or branched alkyl group. The compound shown in formula (I) is also a derivative of 3,4-ethylenedioxythiophene. Hereinafter, "3,4-ethylenedioxythiophene" will sometimes be abbreviated as "EDOT".
[0038] When the first conductive polymer contained in the solid electrolyte layer comprises units of the first monomer, the characteristics of the electrolytic capacitor are improved. In particular, the leakage current of the electrolytic capacitor is significantly reduced, and the withstand voltage characteristic is significantly improved. This improvement in characteristics is believed to be due to the improved orientation of the first conductive polymer resulting from the units of the first monomer, thus improving the film quality of the solid electrolyte layer. Furthermore, it is believed that the change in the orientation of the first conductive polymer makes it difficult for current to flow in the inter-electrode direction. Since the atom X of the first monomer has electron-donating properties, it is possible for interactions to occur between the thiophene skeleton of one molecule and the atoms X of other molecules.
[0039] In the first conductive polymer, only one first monomer may be used, or multiple first monomers may be combined. The units of the first monomer may constitute the entirety of the units used to form the first conductive polymer. The units of the first monomer may constitute, for example, 1 mol% or more, or 10 mol% or more, or 20 mol% or more of the units used to form the first conductive polymer. The units of the first monomer may constitute, for example, 99 mol% or less, or 90 mol% or less, or 80 mol% or less of the units used to form the first conductive polymer.
[0040] In formula (I), m is preferably an integer of 1 or more. For example, m can be an integer from 1 to 5, or an integer from 1 to 3. For example, when X is O (oxygen atom), the first monomer is preferably alkoxyalkyl-EDOT, and when X is S (sulfur atom), the first monomer is preferably alkylthioalkyl-EDOT. It is believed that by introducing an alkylene bond atom X onto the carbon atom of the ethylene, the structural stability of the unit of the first monomer can be improved.
[0041] In formula (I), from the perspective of ease of synthesis, X is preferably O (oxygen atom).
[0042] In formula (I), R1 can have 1 to 10 carbon atoms, or it can be an alkyl group with 1 to 6 carbon atoms. When R1 has 5 or more carbon atoms, the voltage withstand characteristics of electrolytic capacitors are particularly easy to improve.
[0043] For example, in equation (I), the first monomer when m=1 and X=O (oxygen atom) is equation (II):
[0044]
[0045] The alkoxymethyl-3,4-ethylenedioxythiophene shown is alkoxymethyl-EDOT.
[0046] That is, the first monomer may contain at least one selected from the group consisting of alkoxymethyl-EDOT. More than 50 mol% of the first monomer may be alkoxymethyl-EDOT, and more than 70 mol% of the first monomer may be alkoxymethyl-EDOT.
[0047] R1 in formula (II) is defined in the same way as R1 in formula (I), and is a straight-chain or branched alkyl group, wherein the number of carbon atoms in such alkyl group can be 1 to 10 or 1 to 6. That is, the first monomer can be an alkoxymethyl-EDOT in which R1 has 1 to 6 carbon atoms (more specifically, selected from at least one of the group consisting of alkoxymethyl-EDOT in which R1 has 1 to 6 carbon atoms). 50 mol% or more of the first monomer can be an alkoxymethyl-EDOT in which R1 has 1 to 6 carbon atoms, and 70 mol% or more of the first monomer can be an alkoxymethyl-EDOT in which R1 has 1 to 6 carbon atoms.
[0048] Preferred examples of the first monomer include, for instance, methoxymethyl-EDOT of formula (II) where R1 is methyl, ethoxymethyl-EDOT of formula (II) where R1 is ethyl, butylbutoxymethyl-EDOT of formula (II) where R1 is butyl, and hexylhexyloxymethyl-EDOT of formula (II), but the first monomer is not limited to these. However, in these preferred examples, the first monomer more preferably accounts for 50 mol% or more, and even more preferably 70 mol% or more of the first monomer.
[0049] The first conductive polymer may further comprise units of the second monomer. The first conductive polymer may be a copolymer of the first monomer and the second monomer, or a mixture of a polymer comprising the first monomer and a polymer comprising the second monomer. The first conductive polymer may be a copolymer of the first monomer and the second monomer, or a mixture of at least one of a polymer comprising the first monomer and a polymer comprising the second monomer.
[0050] The second monomer is, for example, the following formula (III):
[0051]
[0052] The 3,4-ethylenedioxythiophene (EDOT) shown is of formula (IV) below:
[0053]
[0054] At least one of the group consisting of alkyl-3,4-ethylenedioxythiophene (alkyl-EDOT). EDOT and alkyl-EDOT have chemical structures suitable for forming mixtures of copolymers or polymers with the first monomer.
[0055] In formula (IV), R2 can be, for example, an alkyl group having 1 to 10 carbon atoms, preferably an alkyl group having 1 to 6 carbon atoms. That is, at least a portion of the alkyl-EDOT can be an alkyl-EDOT having 1 to 6 carbon atoms in R2 (more specifically, selected from at least one of the group consisting of alkyl-EDOT having 1 to 6 carbon atoms in R2). 50 mol% or more of the alkyl-EDOT can be an alkyl-EDOT having 1 to 6 carbon atoms in R2, and 70 mol% or more of the alkyl-EDOT can be an alkyl-EDOT having 1 to 6 carbon atoms in R2.
[0056] The number of carbon atoms in R2 in formula (IV) can be in the range of 1 to 4 or 2 to 4, and can be 2 or 3, or 3 or 4.
[0057] The second monomer may contain only EDOT or alkyl-EDOT, or both EDOT and alkyl-EDOT. Furthermore, alkyl-EDOT may contain multiple alkyl-EDOTs with different R2 values.
[0058] The total of the units of the first monomer and the units of the second monomer may constitute 70 mol% or more, or 90 mol% or more, or 95 mol% or more of the units used to form the first conductive polymer. The total of the units of the first monomer and the units of the second monomer may constitute 100% of the units used to form the first conductive polymer.
[0059] The molar ratio (U1 / U2) of the first monomer unit (U1) to the second monomer unit (U2) contained in the first conductive polymer is, for example, in the range of 0.01 to 100, 0.1 to 10, 0.25 to 4, or 0.3 to 3.5. By using both the first monomer unit (U1) and the second monomer unit (U2) within such ranges, it is possible to improve the electrostatic capacitance while reducing leakage current and also improve the withstand voltage characteristics.
[0060] The solid electrolyte layer may comprise a first solid electrolyte layer and a second solid electrolyte layer covering at least a portion of the first solid electrolyte layer. The first solid electrolyte layer covers at least a portion of the dielectric layer. The second solid electrolyte layer is formed on the first solid electrolyte layer, with the first solid electrolyte layer serving as a substrate layer. However, a portion of the second solid electrolyte layer may also be attached to the surface of the dielectric layer. The first conductive polymer is preferably contained at least in the first solid electrolyte layer. It is considered that the first conductive polymer containing the first monomer has a high affinity for the dielectric layer.
[0061] The first solid electrolyte layer can be formed, for example, by chemical polymerization (in-situ polymerization) of the first monomer on the surface of the dielectric layer while the polymer solution containing the first monomer is in contact with the dielectric layer. The polymer solution used in the chemical polymerization may contain, for example, a component that acts as an oxidizing agent, and a material that generates a low-molecular-weight dopant (e.g., an organosulfonate metal salt). Therefore, the first solid electrolyte layer may contain a low-molecular-weight dopant. It should be noted that the molecular weight of the low-molecular-weight dopant may, for example, be 500 or less.
[0062] Low molecular weight dopants refer to all dopants other than high molecular weight dopants, such as p-toluenesulfonic acid, naphthalenesulfonic acid and other organic sulfonic acids, salts of organic sulfonic acids, complexes of organic sulfonic acids, etc.
[0063] Specific examples of the first conductive polymer include: poly(alkoxyalkyl-EDOT) doped with an organosulfonate anion (low molecular weight dopant); copolymers of alkoxyalkyl-EDOT doped with an organosulfonate anion and EDOT; copolymers of alkoxyalkyl-EDOT doped with an organosulfonate anion and alkyl-EDOT; and copolymers of alkoxyalkyl-EDOT doped with an organosulfonate anion and EDOT and alkyl-EDOT. More specifically, polymers doped with an organosulfonate anion and containing at least one unit selected from the group consisting of alkoxymethyl-EDOT with 1 to 6 carbon atoms (e.g., ethoxymethyl-EDOT) can be cited.
[0064] The first solid electrolyte layer may contain a first conductive polymer and a silicon-containing component. It is believed that by including a silicon-containing component in the first solid electrolyte layer, the orientation of the first conductive polymer containing the first monomer unit is more easily varied, resulting in a further significant reduction in leakage current and a further significant improvement in voltage withstand characteristics of the electrolytic capacitor.
[0065] Silicon-containing components can be derived, for example, from silane coupling agents. Silane coupling agents are silane compounds having hydrolyzable groups (e.g., alkoxy groups). From the perspective of reducing ESR and increasing capacity, silane compounds preferably have epoxy or acryloyl groups. As silane coupling agents, only one silane coupling agent can be used, or two or more silane coupling agents can be used in combination.
[0066] Examples of silane compounds with epoxy groups (silane coupling agents) include 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-epoxypropoxypropyltrimethoxysilane (γ-epoxypropoxypropyltrimethoxysilane), 3-epoxypropoxypropylmethyldiethoxysilane, 3-epoxypropoxypropyltriethoxysilane, etc.
[0067] Examples of silane compounds (silane coupling agents) having an acryloyl group include 3-methacryloyloxypropylmethyldimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-methacryloyloxypropylmethyldiethoxysilane, 3-methacryloyloxypropyltriethoxysilane, 3-acryloyloxypropyltrimethoxysilane (γ-acryloyloxypropyltrimethoxysilane), etc.
[0068] Other examples of silane coupling agents include vinyltrichlorosilane, vinyltrimethoxysilane, vinyltriethoxysilane, p-styryltrimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltriethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, and 3-triethoxymethylsilane. Alkyl-N-(1,3-dimethyl-butylene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, hydrochloride salts of N-(vinylbenzyl)-2-aminoethyl-3-aminopropyltrimethoxysilane, 3-ureopropyltriethoxysilane, 3-chloropropyltrimethoxysilane, 3-mercaptopropylmethyldimethoxysilane, 3-mercaptopropyltrimethoxysilane, bis(triethoxysilylpropyl)tetrasulfide, 3-isocyanate propyltriethoxysilane, etc.
[0069] The second solid electrolyte layer comprises a second conductive polymer. Examples of second conductive polymers include polypyrrole, polythiophene, polyaniline, and their derivatives. Derivatives refer to polymers with conductive polymers as their basic backbone. For example, examples of polythiophene derivatives include poly(3,4-ethylenedioxythiophene) (hereinafter also referred to as "PEDOT"). They can be used alone or in combination.
[0070] The second conductive polymer is preferably different from the first conductive polymer. The second conductive polymer preferably contains units of a third monomer. The third monomer can be the second monomer, for example, 3,4-ethylenedioxythiophene (EDOT). It should be noted that the polymer of EDOT is poly(3,4-ethylenedioxythiophene) (PEDOT).
[0071] The second solid electrolyte layer may contain polymeric dopants. The second solid electrolyte layer is formed on top of the first solid electrolyte layer, using the first solid electrolyte layer as a substrate, thus making it suitable for using polymeric dopants. Polymeric dopants help to further improve the voltage withstand characteristics of the electrolytic capacitor.
[0072] Examples of polymeric dopants include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly(2-acrylamide-2-methylpropanesulfonic acid), polyisoprene sulfonic acid, aromatic polyester sulfonic acid, phenolic sulfonic acid varnish resin, and other polymers, as well as their salts and complexes.
[0073] As a preferred example of a second conductive polymer, PEDOT (i.e., PEDOT / PSS) can be cited as an example, which is doped with polystyrene sulfonate (PSS) anions as polymeric dopant.
[0074] In the electrolytic capacitor disclosed herein, there are no particular limitations on the constituent elements other than the solid electrolyte layer, and the constituent elements known to be used in electrolytic capacitors can be applied. These constituent elements will be further described below.
[0075] (Anode)
[0076] The anode material can be a valve-acting metal. Valve-acting metals include titanium (Ti), tantalum (Ta), niobium (Nb), aluminum (Al), and / or alloys containing them. An anode with porous portions can also be formed by sintering particles of the material (e.g., particles of the valve-acting metal). Alternatively, an anode with porous portions can be formed by etching the surface of a metal foil. The dielectric layer formed on the surface of the anode can also be formed by chemically converting the surface of the anode. The method of chemical conversion is not limited, and well-known chemical conversion methods can be applied.
[0077] Capacitors using sintered bodies (e.g., sintered tantalum bodies) as the anode body typically do not contain separators. In capacitors without separators, suppressing leakage current becomes particularly important due to the narrow spacing between the anode body and the cathode lead layer. Therefore, the solid electrolyte layer of a capacitor without separators is particularly preferably configured as described above.
[0078] (Anode wire)
[0079] When the anode body is a sintered body, the anode portion may include an anode wire. The anode wire may also be a wire made of metal. Examples of materials for the anode wire include the aforementioned valve-acting metal, copper, etc. A portion of the anode wire is embedded in the anode body, and the remaining portion protrudes from the end face of the anode body.
[0080] (Solid electrolyte layer)
[0081] The aforementioned solid electrolyte layer can be applied.
[0082] (Cathode lead-out layer)
[0083] The cathode lead-out layer is a conductive layer configured to cover at least a portion of the solid electrolyte layer (or a second solid electrolyte layer). The cathode lead-out layer may comprise a carbon layer formed on the solid electrolyte layer and a metal paste layer formed on the carbon layer. The carbon layer may also be formed from a conductive carbon material such as graphite and a resin. The metal paste layer may be formed from metal particles (e.g., silver particles) and a resin, or it may be formed from, for example, a known silver paste.
[0084] (Cathode lead terminal and anode lead terminal)
[0085] The lead terminals (cathode lead terminals and anode lead terminals) are not particularly limited, and known lead terminals can be used. A portion of the cathode lead terminal is electrically connected to the cathode lead layer. For example, this portion can also be connected to the cathode lead layer through a conductive layer (e.g., a silver paste layer).
[0086] (outer body)
[0087] The outer casing is not limited and any known outer casing may be used. The outer casing may be composed of at least one element selected from the group consisting of a resin composition, a film, and a housing. One example of the outer casing is configured around the capacitor element in such a way that the capacitor element is not exposed on the surface of the electrolytic capacitor. Furthermore, this example of the outer casing is configured to cover a portion of the anode lead frame and a portion of the cathode lead frame. The resin composition used as the outer casing may comprise a resin (insulating resin) and an insulating filler.
[0088] (Manufacturing method)
[0089] Next, an example of a method for manufacturing an electrolytic capacitor will be described. The method for manufacturing an electrolytic capacitor according to this embodiment is a method for manufacturing an electrolytic capacitor including an anode body having a porous portion and a dielectric layer formed on at least a portion of the surface of the porous portion. Hereinafter, this manufacturing method will sometimes be referred to as "manufacturing method (M)".
[0090] The manufacturing method (M) sequentially includes step (i) and step (ii). As described later, according to the manufacturing method (M) including steps (i) and (ii), a solid electrolyte layer comprising a first solid electrolyte layer and a second solid electrolyte layer can be formed. The first solid electrolyte layer comprises a first conductive polymer containing units of a first monomer, and may contain silicon-containing components. By using the first conductive polymer containing units of the first monomer, leakage current is reduced and voltage withstand capability is improved.
[0091] The first solid electrolyte layer is preferably formed, for example, by chemical polymerization (in-situ polymerization). In this case, the first solid electrolyte layer can be uniformly formed using the surface of the intricate porous structure. Therefore, ESR can be reduced and capacity improved. Furthermore, by adding a silane compound to the polymerization solution used to form the first solid electrolyte layer and forming a second solid electrolyte layer, the voltage withstand capability can be improved.
[0092] The following describes process (i) and process (ii).
[0093] (Process (i))
[0094] Step (i) is the step of forming a first solid electrolyte layer covering at least a portion of the dielectric layer. The first solid electrolyte layer comprises a first conductive polymer. Step (i) includes: step (ia), supplying a polymerization liquid (reaction liquid) comprising a first monomer and a silane compound to the surface of the dielectric layer; and step (ib), forming the first solid electrolyte layer by polymerizing the first monomer (and, if other monomers are included, such other monomers) in the supplied polymerization liquid to form the first conductive polymer.
[0095] The polymerization liquid can meet the following conditions (1).
[0096] (1) The proportion of the first monomer in the total monomers of the polymerization liquid is more than 25 mol% or more than 50 mol%, and less than 90 mol% or less than 75 mol%.
[0097] The polymerization solution can satisfy conditions (2) and / or (3) below. For example, it can also satisfy both conditions (2) and (3). In these cases, the polymerization solution can further satisfy condition (1).
[0098] (2) The combined proportion of the first and second monomers in the total monomers in the polymerization liquid is in the range of 80-100 mol%, 90-100 mol%, or 95-100 mol% (e.g., 100 mol%).
[0099] (3) In the polymerization solution, the molar ratio of the first monomer to the second monomer can be in the range of 0.1 to 10 or in the range of 0.25 to 4.
[0100] Silane compounds can be silane coupling agents. In the reaction solution, the value X ((mass of the silane compound) / (total mass of the monomer, oxidant, and liquid medium of the polymerization solution)) can be 0.05 or higher, 0.10 or higher, 0.15 or higher, or 0.20 or lower, or 0.40 or lower, 0.30 or lower, or 0.20 or lower. This value X can be in the range of 0.05 to 0.40, 0.05 to 0.30, or 0.10 to 0.30. By setting this value X within these ranges, capacitors with low ESR, high withstand voltage, and low leakage current can be easily obtained.
[0101] The liquid medium (solvent) of the reaction solution is not particularly limited, as long as it is a liquid medium that can facilitate polymerization without problems. The liquid medium can be water, a mixture of water and a non-aqueous solvent, or a non-aqueous solvent itself. Examples of non-aqueous solvents include organic solvents and ionic liquids. Specifically, examples of non-aqueous solvents include alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, and propylene glycol; amides such as formaldehyde, N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone; esters such as methyl acetate; ethers such as 1,4-dioxane; and ketones such as methyl ethyl ketone.
[0102] The polymerization of monomers can be carried out through chemical polymerization. In the case of chemical polymerization, the polymerization liquid contains an oxidizing agent. As an oxidizing agent, an oxidizing agent capable of polymerizing monomers can be used, or a known oxidizing agent can be used. Examples of oxidizing agents include sulfuric acid, hydrogen peroxide, and metal salts of organosulfonates. Examples of metal ions of metal salts of organosulfonates include iron (III), copper (II), chromium (VI), cerium (IV), manganese (VII), and zinc (II).
[0103] As organosulfonate metal salts, aromatic sulfonate metal salts are preferred, such as toluenesulfonate metal salts, naphthalenesulfonate metal salts, tetrahydronaphthalenesulfonate metal salts, alkylbenzenesulfonate metal salts, and alkoxybenzenesulfonate metal salts. Aromatic sulfonate metal salts function not only as oxidizing agents but also as dopants, thus eliminating the need for additional dopants. Furthermore, aromatic sulfonate metal salts perform excellently as dopants, enabling the formation of high-quality conductive polymers. Iron(III) p-toluenesulfonate is particularly preferred, as it produces conductive polymers with excellent conductivity and heat resistance.
[0104] The polymerization solution can contain other components as needed. For example, the polymerization solution can contain low-molecular-weight dopants. It should be noted that examples of low-molecular-weight dopants added to the reaction solution include those already described. By using low-molecular-weight dopants, the polymerization solution can easily penetrate into the porous structure.
[0105] The process (ia) can be performed by bringing the dielectric layer on the surface of the anode into contact with the polymerization solution. For example, the polymerization solution can be supplied to the surface of the dielectric layer by immersing the anode in the polymerization solution.
[0106] Process (ib) can be carried out by a polymerization reaction occurring while the dielectric layer on the surface of the anode is in contact with the polymerization solution. The polymerization reaction can be initiated by placing the polymerization solution in the atmosphere or by taking measures to promote the reaction. For example, heat treatment can also be performed. Through process (ib), a first solid electrolyte layer is formed.
[0107] (Process (ii))
[0108] Step (ii) is the step of forming a second solid electrolyte layer covering at least a portion of the first solid electrolyte layer. The second solid electrolyte layer comprises a second conductive polymer. The second solid electrolyte layer may comprise the second conductive polymer and a dopant. The second conductive polymer may be the same as or different from the first conductive polymer. In a preferred embodiment, the first conductive polymer is a copolymer of a first monomer and a second monomer, and the second conductive polymer is a polymer of a second monomer doped with a polymeric dopant. Such a second conductive polymer may, for example, be poly(3,4-ethylenedioxythiophene) (PEDOT / PSS) doped with polystyrene sulfonate.
[0109] Step (ii) can be performed by a known method for forming a solid electrolyte layer of an electrolytic capacitor. Step (ii) may sequentially include steps (ii-a) and (ii-b). Step (ii-a) is the process of coating a dispersion containing a second conductive polymer and a dispersion medium onto a first solid electrolyte layer. Step (ii-b) is the process of forming a second solid electrolyte layer by removing at least a portion of the dispersion medium from the coated dispersion.
[0110] Step (ii-a) can be performed by contacting the first solid electrolyte layer formed on the dielectric layer with the dispersion. For example, the first solid electrolyte layer can be immersed in the dispersion, or the dispersion can be coated onto the first solid electrolyte layer. In step (ii-b), the method for removing at least a portion of the dispersion medium coated on the first solid electrolyte layer is not limited, and known methods can be used. For example, the dispersion medium can be removed by heating and / or reducing pressure. Furthermore, the formation steps including steps (ii-a) and (ii-b) can be repeated multiple times. By repeatedly performing this formation step, the second solid electrolyte layer can be thickened.
[0111] The dispersion medium is not limited; water or a mixture of water and an organic solvent can be used. The dispersion may contain dopants. The secondary conductive polymer can also be dispersed in the dispersion medium in particulate form.
[0112] There is no particular limitation on the concentration of the second conductive polymer in the dispersion. This concentration can be in the range of 0.5 to 5.0% by mass (e.g., 1.0 to 3.0% by mass).
[0113] As described above, a solid electrolyte layer comprising a first solid electrolyte layer and a second solid electrolyte layer is formed. Then, the steps required for manufacturing an electrolytic capacitor are performed. These steps are not particularly limited, and known steps for manufacturing electrolytic capacitors can be performed. For example, firstly, a cathode lead layer is formed to cover at least a portion of the solid electrolyte layer (more specifically, the second solid electrolyte layer). This yields a capacitor element. Next, lead terminals are connected to the capacitor element. For example, anode lead terminals are electrically connected to an anode body or anode wire, and cathode lead terminals are electrically connected to the cathode lead layer. Then, a portion of the lead terminals and the capacitor element are encapsulated in an outer casing. This yields a solid electrolytic capacitor.
[0114] Next, an example of a method for manufacturing an electrolytic capacitor will be specifically described with reference to the accompanying drawings. The above description can be applied to the examples described below. Furthermore, the example described below can be modified based on the above description. Additionally, the matters to be described below can be applied to the embodiments described above. Furthermore, in the embodiments described below, non-essential components of the electrolytic capacitor disclosed herein can be omitted. Moreover, for ease of understanding, shapes different from actual shapes are sometimes shown in the following figures.
[0115] (Implementation Method 1)
[0116] Figure 1 A cross-sectional view of an example of the capacitor (C) of Embodiment 1 is shown schematically. Figure 1 The capacitor (solid electrolytic capacitor) 100 includes a capacitor element 110, an outer casing 150, an anode lead terminal 210, and a cathode lead terminal 220. The outer casing 150 is configured to cover a portion of the anode lead terminal 210, a portion of the cathode lead terminal 220, and the capacitor element 110.
[0117] The capacitor element 110 includes an anode portion 111, a dielectric layer 114, and a cathode portion 115. The anode portion 111 includes an anode body 113 and an anode wire 112. The anode body 113 is a rectangular porous sintered body with the dielectric layer 114 formed on its surface. A portion of the anode wire 112 protrudes from one end face of the anode body 113 toward the front surface 100f of the electrolytic capacitor 100. The remaining portion of the anode wire 112 is embedded in the anode body 113.
[0118] The cathode portion 115 includes a solid electrolyte layer 116 configured to cover at least a portion of the dielectric layer 114 and a cathode lead-out layer 117 formed on the solid electrolyte layer 116. The cathode lead-out layer 117 includes, for example, a carbon layer formed on the solid electrolyte layer 116 and a metal particle layer formed on the carbon layer. The metal particle layer is, for example, a metal paste layer (e.g., a silver paste layer) formed using a metal paste.
[0119] The anode lead terminal 210 includes an anode terminal portion 211 and a wire connection portion 212. The anode terminal portion 211 is located on the bottom surface 100b of the electrolytic capacitor 100 (see reference). Figure 2 The cathode wire 112 is exposed. The cathode wire connection portion 212 is connected to the anode wire 112. The cathode lead terminal 220 includes a cathode terminal portion 221 and a connection portion 222. The cathode terminal portion 221 is exposed on the bottom surface 100b of the electrolytic capacitor 100. The connection portion 222 is electrically connected to the cathode lead layer 117 (cathode portion 115) through the conductive layer 141.
[0120] Figure 2 An enlarged view schematically showing portions of the anode body 113, the dielectric layer 114, and the solid electrolyte layer 116. (Refer to...) Figure 2 The anode body 113 has at least a porous portion 113a on its surface. A dielectric layer 114 is formed on the surface of the porous portion 113a. A solid electrolyte layer 116 comprises a first solid electrolyte layer 116a and a second solid electrolyte layer 116b. The first solid electrolyte layer 116a is formed on the dielectric layer 114. The second solid electrolyte layer 116b is formed on the first solid electrolyte layer 116a. That is, the first solid electrolyte layer 116a and the second solid electrolyte layer 116b are sequentially stacked on the dielectric layer 114.
[0121] The solid electrolyte layer 116 of the capacitor 100 is formed by the method described above. Specifically, step (i) forms a first solid electrolyte layer 116a, and step (ii) forms a second solid electrolyte layer 116b. The first solid electrolyte layer 116a contains a first conductive polymer and may also contain a silicon-containing component. The second solid electrolyte layer 116b contains a second conductive polymer.
[0122] (Postscript)
[0123] The following technology is disclosed through the above description.
[0124] (Technology 1)
[0125] An electrolytic capacitor comprising:
[0126] Anode body with porous portion;
[0127] A dielectric layer formed on at least a portion of the surface of the porous portion; and
[0128] A solid electrolyte layer covering at least a portion of the dielectric layer.
[0129] The solid electrolyte layer comprises a first conductive polymer containing units of a first monomer.
[0130] The first monomer is selected from the following formula (I):
[0131]
[0132] At least one of the compounds shown in the group.
[0133] In the formula (I), m is an integer from 0 to 10, X is O or S, and R1 is a straight-chain or branched alkyl group.
[0134] (Technology 2)
[0135] According to the electrolytic capacitor of technology 1, m is an integer from 1 to 5, X is 0, and the number of carbon atoms in R1 is 1 to 10.
[0136] (Technology 3)
[0137] According to the electrolytic capacitor of technique 1 or 2, the first single cell is selected from the following formula (II):
[0138] At least one of the groups consisting of alkoxymethyl-3,4-ethylenedioxythiophene shown.
[0139] (Technology 4)
[0140] The electrolytic capacitor according to any one of techniques 1 to 3, wherein the first monomer is at least one selected from the group consisting of alkoxymethyl-3,4-ethylenedioxythiophene having 1 to 6 carbon atoms in R1.
[0141] (Technology 5)
[0142] The electrolytic capacitor according to any one of techniques 1 to 4, wherein the first conductive polymer further comprises units of a second monomer.
[0143] The second monomer comprises at least one selected from the group consisting of 3,4-ethylenedioxythiophene and alkyl-3,4-ethylenedioxythiophene.
[0144] (Technology 6)
[0145] According to the electrolytic capacitor of technology 5, the molar ratio (U1 / U2) of the first monomer unit (U1) to the second monomer unit (U2) contained in the first conductive polymer is in the range of 0.01 to 100.
[0146] (Technology 7)
[0147] The electrolytic capacitor according to any one of techniques 1 to 6, wherein,
[0148] The solid electrolyte layer comprises a first solid electrolyte layer and a second solid electrolyte layer covering at least a portion of the first solid electrolyte layer.
[0149] At least the first solid electrolyte layer contains the first conductive polymer.
[0150] (Technology 8)
[0151] According to the electrolytic capacitor of Technique 7, the first solid electrolyte layer comprises a low-molecular-weight dopant.
[0152] (Technology 9)
[0153] According to the electrolytic capacitor of technology 8, the first conductive polymer is doped with an organic sulfonate anion as the low molecular weight dopant, and contains at least one unit selected from the group consisting of alkoxymethyl-3,4-ethylenedioxythiophene with 1 to 6 carbon atoms of R2.
[0154] (Technology 10)
[0155] The electrolytic capacitor according to any one of techniques 7 to 9, wherein the first solid electrolyte layer comprises the first conductive polymer and a silicon-containing component.
[0156] (Technology 11)
[0157] According to the electrolytic capacitor of technology 10, the silicon-containing component is derived from a silane coupling agent.
[0158] (Technology 12)
[0159] The electrolytic capacitor according to any one of techniques 7 to 11, wherein,
[0160] The second solid electrolyte layer contains a second conductive polymer that is different from the first conductive polymer.
[0161] The second conductive polymer contains units of a third monomer.
[0162] The third monomer comprises 3,4-ethylenedioxythiophene.
[0163] (Technology 13)
[0164] According to the electrolytic capacitor of technology 12, the second solid electrolyte layer comprises a polymeric dopant.
[0165] (Technology 14)
[0166] According to the electrolytic capacitor of technology 13, the second conductive polymer comprises poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonate anions as the polymer dopant.
[0167] [Example]
[0168] The electrolytic capacitors of this disclosure are described in more detail through examples. In the following examples, multiple (n=40) electrolytic capacitors are fabricated and evaluated.
[0169] (Capacitors A1~A7, B1)
[0170] The capacitors are fabricated in the following order. First, a tantalum sintered body (porous body) with a portion of the anode wire embedded is prepared as the anode body. By anodizing the surface of the tantalum sintered body, a dielectric layer containing tantalum oxide is formed on the surface of the anode body.
[0171] <First Solid Electrolyte Layer>
[0172] Next, a first solid electrolyte layer is formed on the surface of the dielectric layer by chemical polymerization. First, a polymerization solution is prepared. The polymerization solution is prepared by adding ferric p-toluenesulfonate (oxidant), 3-acryloyloxypropyltrimethoxysilane (silane compound), and monomers to ethanol (liquid medium) and mixing them.
[0173] In Example 1 (capacitor A1), only the first monomer was used; in Comparative Example 1 (capacitor B1), only the second monomer was used; and in Capacitors A2 to A7 of Examples 2 to 7, a mixture of the first and second monomers was used. The polymers were prepared such that the mole fractions (U1 / U2) of the first and second monomers in the polymerization solution were the values shown in Table 1.
[0174] In capacitors A1 to A7 of Examples 1 to 7, ethoxymethyl-EDOT represented by formula (II) and R1 being ethyl is used as the first monomer.
[0175] In capacitor A8 of Example 8, the first monomer is butoxymethyl-EDOT represented by formula (II) and R1 is butyl.
[0176] In the capacitor A9 of Example 9, the first monomer is hexyloxymethyl-EDOT represented by formula (II) with R1 being hexyl.
[0177] In capacitors A2~A9 and B1, the second monomer used is 3,4-ethylenedioxythiophene (EDOT). The value X is (mass of the silane compound) / (total mass of the monomer, oxidant, and liquid medium of the reaction solution).
[0178] [Table 1]
[0179]
[0180] Next, the tantalum sintered body is immersed in the polymerization solution for about 3 to 10 seconds. Then, after being lifted out of the polymerization solution, the tantalum sintered body is heated at 210°C for 3 minutes, thereby causing the monomers to polymerize. In this way, a first solid electrolyte layer comprising a first conductive polymer and a silicon-containing component is formed.
[0181] <Second Solid Electrolyte Layer>
[0182] In capacitors A1, A2, A4, A6, A8, A9, and B1 of Examples 1, 2, 4, 6, 8, 9, and Comparative Example 1, a second solid electrolyte layer was formed using a dispersion of a second conductive polymer. Specifically, firstly, a tantalum sintered body was immersed in the dispersion of the second conductive polymer for approximately 3 to 10 seconds, and then the tantalum sintered body was removed from the dispersion. Next, the tantalum sintered body removed from the dispersion was heated at 180°C for 20 minutes, thereby forming the second solid electrolyte layer. The second conductive polymer used was PEDOT / PSS.
[0183] Next, a cathode lead-out layer is formed on the second conductive polymer layer. This forms a capacitor element. Then, lead terminals are connected to the capacitor element. Next, a portion of the lead terminals and the capacitor element are sealed using an outer casing. This manufactures an electrolytic capacitor (capacitors A1 to A9, B1).
[0184] The capacitors obtained as described above were subjected to a curing treatment at 120°C and a rated voltage of 35V for 90 minutes. Then, after the cured capacitors were left at room temperature for more than one hour, the capacitance (Cap), leakage current (LC), and withstand voltage characteristics were measured using the following method.
[0185] [evaluate]
[0186] (Leakage current (LC))
[0187] For each of the 40 capacitors fabricated, a voltage of 35V was applied between the anode and cathode leads, and the leakage current (LC) was measured after 120 seconds. The median value was then determined. The relative values of the LC value of sample B1 in Comparative Example 1, set to 100, are shown in Table 1. The smaller the value, the smaller the leakage current, and the better the performance of the electrolytic capacitor.
[0188] (Capacitance)
[0189] For each of the 40 capacitors fabricated, the capacitance (Cap) at a frequency of 120Hz was measured using a 4-terminal LCR meter, and the average value was calculated. The relative values of sample B1 from Comparative Example 1 with a Cap value set to 100 are shown in Table 1. A higher value indicates a larger capacitance and superior performance of the electrolytic capacitor.
[0190] (Voltage withstand characteristic (Vbd))
[0191] For each of the 40 capacitors fabricated, a voltage was applied at a rate of 1.0 V / s, and the voltage was measured when an overcurrent of 0.5 A flowed through the capacitor. The average value was then calculated. The relative values of the capacitor B1 of Comparative Example 1 with a Vbd value of 100 are shown in Table 1. The larger the value, the better the voltage withstand characteristics and the better the performance of the electrolytic capacitor.
[0192] As shown in Table 1, capacitors A1 to A9 exhibit significantly lower capacitance (LC) and significantly improved voltage withstand characteristics compared to capacitor B1. In particular, when a copolymer of the first and second monomers is used as the first conductive polymer, an improvement in capacitance is observed. The U1 / U2 ratio is especially excellent in the range of, for example, 0.3 to 3.5. Furthermore, in Example 9, where R1 has 5 or more carbon atoms (i.e., 6 carbon atoms), the voltage withstand characteristics are particularly significantly improved.
[0193] The invention has been described through the present preferred embodiments, but such disclosure should not be interpreted restrictively. Various modifications and alterations will undoubtedly be apparent to those skilled in the art upon reading the foregoing disclosure. Therefore, the appended claims should be construed as including all modifications and alterations without departing from the true spirit and scope of the invention.
[0194] Industrial availability
[0195] The electrolytic capacitor disclosed herein has low leakage current, high voltage withstand characteristics, and high reliability. Such an electrolytic capacitor is suitable for applications involving connection to electronic circuits, and can suppress malfunctions in electronic circuits. It should be noted that the applications of the electrolytic capacitor are not limited to these.
[0196] Explanation of reference numerals in the attached figures
[0197] 100 Electrolytic Capacitor
[0198] 113 Anode
[0199] 113a Porous section
[0200] 114 Dielectric layer
[0201] 116 Solid electrolyte layer
[0202] 116a First solid electrolyte layer
[0203] 116b Second solid electrolyte layer
Claims
1. An electrolytic capacitor comprising: Anode body with porous sections; A dielectric layer formed on at least a portion of the surface of the porous portion; and A solid electrolyte layer covering at least a portion of the dielectric layer. The solid electrolyte layer comprises a first conductive polymer containing units of a first monomer. The first monomer is selected from the following formula (I): At least one of the compounds shown in the group. In the formula (I), m is an integer from 0 to 10, X is O or S, and R1 is a straight-chain or branched alkyl group.
2. The electrolytic capacitor according to claim 1, wherein, m is an integer from 1 to 5, X is 0, and the number of carbon atoms in R1 is from 1 to 10.
3. The electrolytic capacitor according to claim 1, wherein, The first monomer is selected from the following formula (II): At least one of the groups consisting of alkoxymethyl-3,4-ethylenedioxythiophene shown.
4. The electrolytic capacitor according to claim 1, wherein, The first monomer is at least one selected from the group consisting of alkoxymethyl-3,4-ethylenedioxythiophene with 1 to 6 carbon atoms of R1.
5. The electrolytic capacitor according to claim 1, wherein, The first conductive polymer also contains units of the second monomer. The second monomer comprises at least one selected from the group consisting of 3,4-ethylenedioxythiophene and alkyl-3,4-ethylenedioxythiophene.
6. The electrolytic capacitor according to claim 5, wherein, The molar ratio (U1 / U2) of the first monomer unit (U1) to the second monomer unit (U2) contained in the first conductive polymer is in the range of 0.01 to 100.
7. The electrolytic capacitor according to claim 1, wherein, The solid electrolyte layer comprises a first solid electrolyte layer and a second solid electrolyte layer covering at least a portion of the first solid electrolyte layer. At least the first solid electrolyte layer contains the first conductive polymer.
8. The electrolytic capacitor according to claim 7, wherein, The first solid electrolyte layer contains low-molecular-weight dopants.
9. The electrolytic capacitor according to claim 8, wherein, The first conductive polymeric doped organic sulfonate anion serves as the low molecular weight dopant and comprises at least one unit selected from the group consisting of alkoxymethyl-3,4-ethylenedioxythiophene with R1 having 1 to 6 carbon atoms.
10. The electrolytic capacitor according to claim 7, wherein, The first solid electrolyte layer comprises the first conductive polymer and a silicon-containing component.
11. The electrolytic capacitor according to claim 10, wherein, The silicon-containing component is derived from a silane coupling agent.
12. The electrolytic capacitor according to claim 7, wherein, The second solid electrolyte layer contains a second conductive polymer that is different from the first conductive polymer. The second conductive polymer contains units of a third monomer. The third monomer comprises 3,4-ethylenedioxythiophene.
13. The electrolytic capacitor according to claim 12, wherein, The second solid electrolyte layer contains a polymeric dopant.
14. The electrolytic capacitor according to claim 13, wherein, The second conductive polymer comprises poly(3,4-ethylenedioxythiophene) doped with polystyrene sulfonate anions as the polymer dopant.
Citation Information
Patent Citations
JP1975093915A
Resin composition, laminate structure, cable, tube, and method for manufacturing resin composition
JP2024051299A